A preliminary examination of gut microbiota and emotion regulation in 2- to 6-year-old children - Faulkner, Paul; Costabile, Adele; Imakulata, Florencia; Pandey, Neeraj; Hepsomali, Piril (Frontiers in Developmental Psychology, 2024)
It is well known that having maladaptive emotion regulation skills during childhood may predict mental health issues later in life, therefore, establishing links with gut microbiome could help develop gut -derived interventions directed at improving maladaptive emotion regulation skills during this critical developmental period. While differences in gut microbiome diversity and composition have been associated with several mental health problems in adults and in infants, the current study is the first one to examine whether the gut microbiome diversity and composition are related to emotional regulation abilities during early childhood. In the current cross-sectional study, mothers of seventy-three children aged 2 to-6 years completed several questionnaires assessing their child's and their own emotion regulation skills and mental health, provided a stool sample from their child (via at-home gut microbiome testing kits), and reported on their child's dietary intake. Results revealed that compared to children in the low maladaptive emotion regulation group, alpha diversity, relative abundance of butyrateproducing genera (Butyricicoccus and Odoribacter), and vitamin synthesis scores (Vitamins B2, B3, B6, and B9) were significantly lower in the high maladaptive emotion regulation group.These findings suggest that maladaptive emotion regulation skills link to gut microbiome alterations in early childhood, a crucial time of both brain and gut-immune development,hence, may open the way to the development of early novel (dietary or pre/probiotic) interventions.